The first Ukrainian-Swedish Workshop “New approaches to diagnostics and treatment of cancer” (Experimental Oncology, 2011)
On13–14, June 2011, at the R.E. Kavetsky Institute of Experimental Pathology, Oncology and Radiobiology of National Academy of Sciences of Ukraine the first Ukrainian-Swedish Workshop “New approaches to diagnostics and treatment of cancer” was held. Karolinska Institutet (Sweden) and Odesa National Medical University were the co-organizers of the Workshop.